I dati INVALSI come strumento per migliorare la didattica della Matematica nella scuola primaria IV Seminario "I dati INVALSI: uno strumento per la ricerca e la didattica" - Falzetti, Patrizia (INVALSI per la Ricerca, 2021)
Primary school is considered very worthy for all learning process; actually, one of its goals is to assist pupils in developing basic skills, such as writing, reading a numeracy, before dealing with other subjects for a successful lifelong learning career. This book aims to provide ideas and suggestions in order to improve teaching in Mathematics at primary school, by collecting some studies submitted at IV edition of the Seminar "INVALSI data: a research and teaching tool" held in Roma in November 2019. Thanks to INVALSI data, researchers and teachers can strengthen the necessary partnership to wonder about numeracy learning processes and to improve teaching activities.